Lover bounsd for the data complexity of correlation attacks on stream ciphers over fields of order 2^r - Олексійчук, Антон Миколайович; Поремський, Михайло Васильович (Ukrainian Information Security Research Journal, 2017)
Correlation attacks are one of the most powerful attacks on stream ciphers, and methods of building such kind of attacks and security proofs of stream ciphers against them form a developed direction of modern cryptography. Over the past few years in connection with emergence of world-oriented stream ciphers, methods for building correlation attacks based on solving systems of linear equations corrupted by noise over finite fields or residue rings of order are developed. In this article we investigate two such methods, the first of them consists of solving these systems of equations over fields of order , where , and the second one – in solving analogous systems of equations over a field of two elements. The obtained results can be used in security proofs of word-oriented stream ciphers against modern correlation attacks.